Learning Video Media Using Prezi on Our Friends Environment Theme - Divayuda, I Putu Gede Bagus Tedja; Wibawa, I Made Citra; Rati, Ni Wayan (Universitas Pendidikan Ganesha, 2021)
This research is based on the low attention of students on the implementation of learning using the powerpoint application, causing a lack of understanding of students and causing repetition in the explanation of learning materials delivered by educators. The purpose of this research is to produce a video learning media product using Prezi for fifth grade elementary school students on the Environmental Theme of Sahabat Kita, a valid sub-theme of Environmental Preservation Efforts. This type of research is research and development carried out using the ADDIE model. In the Implementation Phase, the test of learning video media products involving students was not carried out due to the Covid-19 pandemic conditions. The data collection method used is in the form of an assessment instrument. The subjects of this study were two subject content experts and two learning media experts. The technique used in conducting data analysis on the validity test of learning video media using Prezi is the Mean formula, the formula for calculating the percentage of each subject, and the overall percentage formula for the subject. The results of subject content validity conducted by two subject content experts obtained a total percentage of 94.53% with very good qualifications. The results of the validity of the learning video media conducted by two learning media experts obtained a total percentage of 95.83% with very good qualifications. Thus, it can be concluded that the learning video media using Prezi that has been developed is valid, so it is feasible to use it to support the learning process on the Environmental Theme of Our Friends, the Sub-theme of Environmental Preservation for Class V Elementary School.